Природата како извор на национален симбол на државата: „Случај Африка“ - Nature as a Source of National Symbols: ‘Case Study—Africa’ - Nikola Stojanoski (Македонски хералд - Macedonian Herald, 2019)
The goals of the analysis of the flags of the independent countries in Africa in this review are the colours and their symbolism. The focus is on the colours that symbolize certain natural abundance. The review shows that out of 54 state flags in Africa, 40 have a graphic representation of certain natural or geographical features. The reasons for such a symbolism vary. However, one common mutual and uniting feature of all 40 flags is embracing “pan-African” graphic symbolism and colours in response to the dark colonial past and avoiding certain ethnic elements in these multinational African countries.